GIS-grid-based and multi-criteria analysis for identifying and mapping peat swamp forest fire hazard in Pahang, Malaysia - Setiawan, Iwan; Mahmud, Ahmad Rodzi; Mansor, Shattri; Mohamed Shariff, Abdul Rashid; Nuruddin, Ahmad Ainuddin (Emerald, 2004)
Peat swamp forest fire hazard areas were identified and mapped by integrating GIS-grid-based and multi-criteria analysis to provide valuable information about the areas most likely to be affected by fire in the Pekan District, south of Pahang, Malaysia. A spatially weighted index model was implemented to develop the fire hazard assessment model used in this study. Fire-causing factors such as land use, road network, slope, aspect and elevation data were used in this application. A two-mosaic Landsat TM scene was used to extract land use parameters of the study area. A triangle irregular network was generated from the digitized topographic map to produce a slope risk map, an aspect risk map and an elevation risk map. Spatial analysis was applied to reclassify and overlay all grid hazard maps to produce a final peat swamp forest fire hazard map. To validate the model, the actual fire occurrence map was compared with the fire hazard zone area derived from the model. The model can be used only for specific areas, and other criteria should be considered if the model is used for other areas. The results show that most of the actual fire spots are located in very high and high fire risk zones identified by the model.